A novel wide input range transformerless PV microinverter with natural power decoupling - Osama Elbaksawi; Youssef Nasr Ashour; Ahmed F. Abouzeid; Mahmoud Fawzi (Scientific Reports)
Abstract In this paper, a novel wide range microinverter circuit that can interface with a single-phase grid and operates without a transformer is presented. The proposed topology uses six switches: two of those switches function at line frequency every half cycle while the other switches function at high switching frequency. In the proposed topology, the circuit functions in discontinuous conduction mode (DCM) across all possible operating conditions, ensuring high gain and minimal switching losses. A common connection between the PV panel and the grid exists, ensuring no common mode current. The proposed topology naturally decouples the power between the DC and AC sides without using an active power decoupling circuit. Passive power decoupling techniques implemented using a large electrolytic capacitor which is very well known to have low reliability is also not needed. Thus, the microinverter’s reliability is increased by using thin film capacitors. The analysis and verification of the proposed system are presented in this paper. Additionally, a standalone version of the presented circuit is verified experimentally through a fabricated prototype. In addition to the benefits of the presented circuit, both simulation and experimental data demonstrate that the circuit can operate without requiring a duty cycle constraint, offering significantly greater flexibility and a wider operating range.